Advantages of the moth‐eye patterned sapphire substrate for the high performance nitride based LEDs. Issue 3 (19th March 2014) - Kondo, Toshiyuki; Kitano, Tsukasa; Suzuki, Atsushi; Mori, Midori; Naniwae, Koichi; Kamiyama, Satoshi; Iwaya, Motoaki; Takeuchi, Tetsuya; Akasaki, Isamu
Abstract: We propose moth‐eye patterned sapphire substrate (MPSS) as a solution to improve the light extraction efficiency and to reduce the production cost of LEDs. The MPSS samples' surfaces consisted of a triangular grid of about 375 nm high truncated cones with different pitches of 460 nm, 500 nm, 600 nm, 700 nm and 800 nm. A commercially available patterned sapphire substrate (PSS) and a flat sapphire substrate (FSS) was also used in the experiments for comparison. According to the cathode luminescence observation, the GaN template on MPSS with a thickness of 3 µm showed a threading dislocation density (TDD) of around 1.9 × 108 cm –2 . Transmission electron microscope observation revealed that many of the dislocations were bent and disappeared as loops formed in the vicinity of MPSS cones. On the other hand, PSS required a GaN template thicker than 5µm to achieve a level of TDD equal to MPSS. The LED on MPSS with a pitch of 600 nm showed the highest light output power among the evaluated LEDs as it was 1.89 times higher than that on FSS and 1.05 times higher than that on PSS. The pitch dependence of the light output improvement agrees with the pitch dependence of the simulated transmissivity at the GaN/sapphire interface. As a result of our comparison, we concluded that MPSS provides the most cost effective solution for high performance LEDs.